Gladiator [videorecording (Blu-Ray)] - Scott, Ridley; Crowe, Russell, 1964-; Phoenix, Joaquin; Nielsen, Connie, 1965- (Paramount Home Entertainment, 2017)
A man robbed of his name and his dignity strives to win them back, and gain the freedom of his people. In the year 180, the death of the emperor throws the Roman Empire into chaos. Maximus is set to be executed. He escapes, but is captured by slave traders. Renamed Spaniard and forced to become a gladiator, Maximus must battle to the death with other men for the amusement of paying audiences.